Implementasi Kebijakan Tentang Penegakan Disiplin Guru dan Peserta Didik di Sekolah - Rodia Rotani Rianda; Bella Anggraini; Hanestesia Zahara; Yogi Permana; Lara Dwi Alma (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to understand, review, explore, and describe the implementation of policies regarding the enforcement of teacher and student discipline in elementary schools and is expected to find policies that support the success of enforcing teacher and student discipline. This study was conducted using a Systematic Literature Review (SLR) in journals that are appropriate for Elementary Schools, subjects consisting of principals, teachers, educational staff, and students. Data in this study were obtained through Identification of Literature Sources, Determination of Inclusion and Exclusion Criteria, Tools (Mendeley). The findings of the study conducted by the author indicate that the enforcement of teacher and student discipline is carried out through a number of policies, namely: 1) Policies related to the enforcement of teacher and student discipline, 2) Establishing rules at school and in the classroom, 3) Monitoring the disciplinary behavior of teachers and students by making a monitoring book of their daily activities, 4) Imposing sanctions for violations, 5) Involving the principal, teachers, and educational staff. Furthermore, parental involvement and collaboration with external parties are also supporting factors in creating an orderly, safe, and conducive learning environment. Regular evaluation of implemented policies is also crucial to ensure their relevance and effectiveness. Fair and transparent reward and punishment practices contribute to increased student awareness and motivation to comply with school regulations. A culture of discipline consistently cultivated from an early age significantly contributes to positive character development and the overall improvement of the quality of basic education. Implementation requires ongoing training and mentoring for teachers and other educational staff to equip them with the capacity to implement a humanistic yet firm approach.